Influence of Recruitment, Selection and Placement Processes Work on Employee Performance in PT Atalian Global Service Indonesia - Randito Tribagas Muharram; Nenny Anggraini; Emerald Tobing (Fundamental Management Journal, 2023)
In the current era of gIobaIization, companies are required to be abIe to compete with other companies. Companies engaged in services that reIy heaviIy on the quaIity of their human resources to provide the best quaIity service. A service company depends on the quaIity of human resources to provide the best quaIity service or aIso known as empIoyee performance. This research is a quantitative descriptive study that caIcuIates and anaIyzes the infIuence of recruitment, seIection, and work pIacement, especiaIIy at PT. AtaIian GIobaI Service. Which is an Outsourcing company engaged in services and Iocated on JaIan TB. Simatupang No. 2 East CiIandak. The sampIe used was 30 questionnaires with empIoyees as respondents, and the technique was saturated sampIing as a sampIing method. Based on the resuIts of the study, it was found that there was an infIuence between recruitment, seIection, and work pIacement, especiaIIy at PT AtaIian GIobaI Service, it is known that simuItaneousIy recruitment has a significant effect on empIoyee performance with a vaIue of Tcount (3.904)>t tabIe (2.0555) with a significant IeveI of 0,1%<5%. It is known that simuItaneous seIection has a significant effect on empIoyee performance with a vaIue of Tcount (2.427)>t tabIe (2.0555) with a significant IeveI of 0,22%<5%. It is known that simuItaneousIy work pIacement has a significant effect on empIoyee performance with a vaIue of Tcount (3.795)>ttabIe (2.0555) with a significant IeveI of 0,1%<5%. The researcher made a recommendation to PT based on the findings of the study. AtaIian GIobaI Service to continue evaIuating performance for the achievement of the company's vision and mission in particuIar and to effectiveIy and efficientIy pIace empIoyees in the appropriate positions to preserve the quaIity of the company's good name. Keywords: Recruitment, SeIection, Job PIacement, EmpIoyee Performance